Bacterial Infections Complicating Tongue Piercing - Catherine HY Yu; Brian J Minnema; Wayne L Gold (Canadian Journal of Infectious Diseases and Medical Microbiology)
Tongue piercing has become an increasingly popular form of body art. However, this procedure can occasionally be complicated by serious bacterial infections. The present article reports a case of prosthetic valve endocarditis caused by a Gemella species in a patient with a pierced tongue, and reviews 18 additional cases of local and systemic bacterial infections associated with tongue piercing. Infections localized to the oral cavity and head and neck region included molar abscess, glossal abscess, glossitis, submandibular lymphadenitis, submandibular sialadenitis, Ludwig’s angina and cephalic tetanus. Infections distal to the piercing site included eight cases of infective endocarditis, one case of chorioamnionitis and one case of cerebellar abscess. Oropharyngeal flora were isolated from all cases. While bacterial infections following tongue piercing are rare, there are reports of potentially life-threatening infections associated with the procedure. Both piercers and their clients should be aware of these potential complications, and standardized infection prevention and control practices should be adopted by piercers to reduce the risk.